TEKNOLOGI PEMANFAATAN LIMBAH IKAN MENJADI PUPUK ORGANIK CAIR UNTUK MENINGKATKAN PENDAPATAN RUMAH TANGGA DI DESA MUNTAI KECAMATAN BANNTAN KABUPATEN BENGKALIS - Sukmiwati, Mery; Sari, N. Ira; Diharmi, Andarini (Universitas Negeri Medan, 2024)
Muntai Village is a coastal area with high potential sea conditions to produce maximum fish catch where most of the people are fishermen. Purpose of Devotional Activities can know and understand the way of making organic liquid fertilizer derived from the fish wast stomach catches. Increase the knowledge and skill of extension participants about the techniques of making microorganisms, how to use liquid organic fertilizer and know the right time when fertilizing. Add knowledge, skills, and can provide solutions for processing fisherman/housewives to be able to overcome the scarcity of fertilizer in market. Benefits activity is to increase knowledge about the manufacture of liquid organic fertilizer so that the resulting fertilizer can be sold, thus will be able to increase household income. The results of this training activity can be explained as follows: PKK chairman and the PKK mothers and all the trainee, members give positive feedback on the implementation of this activity, with high enthusiasm visible while the training activities take place. The village head and staff have provided assistance in the facility or the morale so that this activity can be done well in accordance with the planned schedule. There were 32 participants consisting of PKK mothers, processing fisherman in the village of Muntai, Kelurahan Bantan, Bengkalis District in accordance with the target to be achieved. The participants of science and technology implementation demonstrated sincerity during the on going event, starting from the presentation of the material, followed by demonstration activities and then ended with practice. Visible participants are very interested in the material given so that the participants are active in the discussions and question and answer between the participants and the implementing team